Soft Mobility and Geoheritage: E-Biking as a Tool for Sustainable Tourism in Mountain Environments - Antonella Senese; Manuela Pelfini; Piera Belotti; Luca Grimaldi; Guglielmina Diolaiuti (Tourism and Hospitality, 2025)
The increasing popularity of e-biking and e-mountain biking offers new opportunities for sustainable tourism and environmental education, particularly in mountain regions. This study focuses on the Italy–Switzerland “E-Bike” project, which integrates e-bike-friendly routes with scientific and cultural education across the Alps. By analyzing key points of interest along the routes, particularly glaciers and earth pyramids in Lombardy, we explore strategies for sustainable management, conservation, and public engagement. Glaciers (Forni and Ventina), facing rapid retreat due to climate change, represent sensitive environments requiring monitoring and visitor regulation. Similarly, earth pyramids in Postalesio exemplify fragile landforms shaped by erosion, requiring visitor management. This study highlights the need for strategic promotion, clear scientific communication, and sustainable tourism practices to balance conservation with accessibility. E-biking facilitates low-impact exploration of geosites, enhancing public awareness of environmental challenges while minimizing ecological footprints. Innovative digital tools (QR-coded virtual guides) enhance visitor education and engagement. By integrating e-bike tourism with geoheritage conservation, this study proposes guidelines for managing soft mobility in mountain areas, combining conservation needs with accessibility, and fostering public engagement. These findings contribute to broader discussions on sustainable tourism development, offering a replicable model for other regions seeking to harmonize recreation with environmental stewardship.